Myocardial extracellular volume fraction analysis in doxorubicin-induced beagle models: comparison of dual-energy CT with equilibrium contrast-enhanced single-energy CT - Zhou, Z.; Gao, Y.; Wang, H.; Wang, W.; Zhang, H.; Wang, S.; Sun, Zhonghua; Xu, L. (AME Publishing Company, 2021)
Background: Dual-energy CT (DECT) permits the simultaneous operation of two different kV levels, providing a potential method toward the assessment of diffuse myocardial fibrosis. The purpose of this study was to determine the accuracy of DECT for evaluation of the myocardial extracellular volume (ECV) fraction in comparison with single-energy CT (SECT).